Same-day combined endoscopic retrograde cholangiopancreatography and cholecystectomy: Achievable and minimizes costs. Issue 3 (March 2015) - Wild, Jeffrey L.; Younus, M. Jabran; Torres, Denise; Widom, Kenneth; Leonard, Dianne; Dove, James; Hunsinger, Marie; Blansfield, Joseph; Diehl, David L.; Strodel, William; Shabahang, Mohsen M.
Abstract : BACKGROUND: It is estimated that choledocholithiasis is present in 5% to 20% of patients at the time of laparoscopic cholecystectomy (LC). Several European studies have found decreased length of stay (LOS) when performing LC and intraoperative endoscopic retrograde cholangiopancreatography (ERCP) on the same day for choledocholithiasis. In the United States, common bile duct stones are usually managed preoperatively and typically on a day separate from the day LC was performed. Our aim was to evaluate LOS and total hospital cost for separate-day versus same-day ERCP/cholecystectomy. METHODS: This was a retrospective study of patients undergoing ERCP and cholecystectomy during the same admission for the management of choledocholithiasis from 2010 to 2014 at Geisinger Medical Center. The separate-day group underwent ERCP at least 1 day before cholecystectomy and often underwent two separate anesthesia events, while the same-day group had ERCP and cholecystectomy performed on the same day under one general anesthesia event. The primary outcome measured was LOS. RESULTS: The study population included 240 patients. There were 175 patients in the separate-day group and 65 patients in the same-day group. Median age was similar between the two groups. The separate-day group had a median of one minor comorbidity compared with zero within the same-day group using the Charlson Comorbidity Index. Overall, LOS for the separate-day group was 5 days compared with 3 days in the same-day group ( p < 0.0001). There was no difference in conversion rates to open cholecystectomy between the two groups (14% in the separate-day vs. 12% in the same-day group). Total median hospital cost for the separate-day group was 102, 537 compared with 90, 269 in the same-day group ( p < 0.0001). CONCLUSION: Same-day ERCP and cholecystectomy is feasible and minimizes costs. Same-day procedures decreased hospital LOS by 2 days and had approximately 12, 000 in cost savings. Future goals include a multidisciplinary protocol to study outcomes in larger numbers. LEVEL OF EVIDENCE: Therapeutic study, level IV. Economic study, level III.